Jewish and Christian communal identities in the Roman world - Furstenberg, Yair. (Ancient Judaism and Early Christianity, 2016)
Jews and Christians under the Roman Empire shared a unique sense of community. Set apart from their civic and cultic surroundings, both groups resisted complete assimilation into the dominant political and social structures. However, Jewish communities differed from their Christian counterparts in their overall patterns of response to the surrounding challenges. They exhibit diverse levels of integration into the civic fabric of the cities of the Empire and display contrary attitudes towards the creation of trans-local communal networks. The variety of local case studies examined in this volume offers an integrated image of the multiple factors, both internal and external, which determined the role of communal identity in creating a sense of belonging among Jews and Christians under Imperial constraints.